2006
DOI: 10.1089/thy.2006.16.357
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine Acutely Increases Blood Flow in the Ventricles and Kidneys of Anesthesized Rabbits

Abstract: Thyroid hormone (triiodothyronine [T(3)]) has various nongenomic effects, including alterations in glucose and fatty acid metabolism, augmentation of intracellular Ca(2+), enhancement of myocardial contractility, and vascular dilatation. However, its effect on regional blood flow remains to be established. We have measured the effect of T(3) on blood flow in major organs of anesthetized rabbits in vivo using the microsphere method. Under artificial respiration, nonradioactive microspheres (5 x 10(5)) labeled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Administration of T3 in vivo in the circulation of major organs of anesthetized rabbits is associated with a vasodilatory response that occurs preferentially in the ventricles and kidneys, but not in the atria or skeletal muscle [44]. The observation of a vasodilatory response induced by TH in coronary arteries is in line with previous reports by Yoneda et al that showed that a bolus injection of T3 or T4 in rat coronary arteries elicited a transient, dose-dependent decrease in coronary perfusion pressure, as well as an increase in arterial vasodilation [45].…”
Section: Thyroid Hormones and The Cardiovascular Systemmentioning
confidence: 99%
“…Administration of T3 in vivo in the circulation of major organs of anesthetized rabbits is associated with a vasodilatory response that occurs preferentially in the ventricles and kidneys, but not in the atria or skeletal muscle [44]. The observation of a vasodilatory response induced by TH in coronary arteries is in line with previous reports by Yoneda et al that showed that a bolus injection of T3 or T4 in rat coronary arteries elicited a transient, dose-dependent decrease in coronary perfusion pressure, as well as an increase in arterial vasodilation [45].…”
Section: Thyroid Hormones and The Cardiovascular Systemmentioning
confidence: 99%
“… 23 An animal study also showed that thyroid hormones (eg, T3) can increase in blood flow in the ventricles and kidneys, a possible mechanism that underlies T3-induced improvement of cardiac and renal function. 24 Kumar et al have revealed that the patients who received levothyroxine experienced rapid improvement in hemodynamics. 25 In addition, histologic studies have documented the effects of T3 on outer and cortical medullary tubular segments, especially the distal convoluted tubules and proximal tubules.…”
Section: Discussionmentioning
confidence: 99%